Assessment of housing affordability problems among younger working households in greater Kuala Lumpur / Zafirah Al Sadat Binti Zyed - Zyed, Zafirah Al Sadat (2014)

(untitled)
Problems relating to housing affordability are closely linked to economic and social factors. Faced with rising rural urban migration, increasing house price, low income growth and high cost of living, the younger working households (YWH) struggle to own a house especially in the private housing market in urban area. Current housing policies do little to help YWH afford a house. Using an institutional framework, this study argued that the state is responsible for providing adequate housing to all income group particularly low and middle income household. When market conditions fail, the state should be held responsible in maximising housing welfares. The discussion of identifying housing affordability problems among YWH led to two important factors to consider. Firstly, the structural pathways in housing policy and schemes have disappointed YWH because of the difficulties to compete in the open housing market and the gap of affordable housing is yet to be filled by the state. Secondly, the capability of YWH in doing things and not their intention in doing it is influenced by the formal structure. The rational action of YWH in choice of housing leaves no space of desire and passion due to the rules and resources. The dependency of structure and agency in this study demonstrated the outcome of the housing affordability problems. Against this background, the main aim of this study is to examine the problems of housing affordability among YWH. This study further intends to address the policy implications of these problems. Four main research questions were addressed. Firstly, what are the problems faced by YWH in finding affordable housing. Secondly, what are emerging policy and schemes formulated to address these problems. Thirdly, to what extent should the state intervene in these problems and finally how can the state address these problems. Drawing upon a case study of YWH in Greater Kuala Lumpur, questionnaire surveys are conducted amongst 420 respondents through random sampling with pre-determined criteria. Additionally, in-depth interviews were also conducted to gain further insight into these problems. Views of the state concerning key issues in addressing housing affordability problems were also sought. The findings revealed that the main problem faced by YWH is limited supply of affordable housing in the market. Even more, the perceived affordable housing in the market is open to all income groups which suggest that YWH has to compete with other income groups in the open market for homeownership. The state has to a certain degree intervene in the market by introducing National Housing Policy (NHP), My First Home Scheme (MFHS) and 1Malaysia People Housing Scheme (PR1MA) to provide affordable housing to this group of YWH. Nevertheless, this intervention is viewed as insufficient. In conclusion, this study suggests that the state should introduce more housing schemes such as the shared ownership schemes to address these problems. It is also recommended that state should perhaps consider properties to be rented to YWH as well as introducing a comprehensive affordable housing system.